Conceptual Model Design of Assistances System Development for Informatics Proficiency TestBased on Ubiquitous Learning (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Thedevelopment ofInformation and Communication Technologyiscurrentlyinfluencing graduates'competencies ineveryIndonesiaUniversity. Someofthephenomena obtainedinthefieldboth technicallyandnon-technicalinclude:Therearestillfew andtendtohavenoinformationfromthecampusrelated tothecompetenceoflecturersandstudentsinthefieldof informatics. Minimalinformation onthecollaboration between thecampus worldandindustrial fields published inthemedia.Cooperation betweencampus withprofessional associations andindustryassociations inimplementing thelinkandmatch,especiallyin curriculum development,feelargeenoughinfollowing thecertificationtestprofessionalsininformatics,yetseen asystemthatactsasanaggregator,asystemthatbridges between industry andthefieldofcampus. The characteristicsmodeldevelopedinthisresearchbroadly combines threemodelsofinterrelated system development betweentheBorgandGallmodelasthe backbone, Hanafin, andPack asthelearninginteraction process,andthewaterfall modelasthemakingofthe mentoringapplication system.Thefinalresultofthe researchistheestablishmentofconceptualmodeldesign in adigitallearningsystemfromacertificationprogram based onthe  IndustrialProfessionaland Association fields.